(Inter) professionals connected to online collaborative learning: A scoping review (Research, Society and Development, 2021)
Introduction: Online collaborative learning can support interprofessional education (IPE) in health, but barriers to social interaction require facilitating strategies. Objective: To map interprofessional social interaction favorable strategies for collaborative learning in distance education. Methodology: A scoping review based on the recommendations of the Joanna Briggs Institute Manual was used to identify evidence from databases and also the snowball technique. The inclusion criteria were: English language, research question terms and articles published from 2010 to 2020. Results: 12 studies were included in this review. Most studies were from 2011 (4); Canada (5); qualitative research, (11) and addressed two theoretical foundations: Community of Inquiry (4) and Constructivism (3). The main results show that the diversity in the composition of the interprofessional teams ranged from 2 to 10 professions; the most frequent interaction strategies in the studies were forums (6) and facilitators (6) and lack of time was the only barrier to social interaction that coincided in 2 studies. Discussion: The social presence strategies (Element of the Community of Inquiry) revealed in the literature and the parameters mapped in this research composed the facilitators of the social interaction targeted on this review. Final considerations: Articulated interprofessional interaction strategies can support online IPE programs in managing existing barriers. Future research may deepen the understanding of the findings of this study.